2014
DOI: 10.1017/gov.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Municipality Size and Local Office on the Electoral Success of Belgian/Flemish Election Candidates: A Multilevel Analysis

Abstract: This article examines the effect that municipality size and local office have on election candidates’ results. We argue that candidates from the larger municipalities have comparatively larger relevant networks, both in terms of constituents and party grassroots volunteers. In addition, these candidates appeal to a relatively larger share of voters within the constituency. We expect that the relative size of the candidates’ municipality will have a positive effect on the relative number of preferential votes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
1
31
1
Order By: Relevance
“…First, over the last years, a change in the formal rules has modified the access for incumbents to candidate lists. Earlier studies on the use of preference votes in Belgium (André et al, 2012;Thijssen, 2013;Put and Maddens, 2015) have shown that the presence of incumbents on the list of candidates has a positive effect on the use of preference votes. A change to the legislation, however, has reduced the capacity of parties to fill in their lists with a lot of such candidates.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…First, over the last years, a change in the formal rules has modified the access for incumbents to candidate lists. Earlier studies on the use of preference votes in Belgium (André et al, 2012;Thijssen, 2013;Put and Maddens, 2015) have shown that the presence of incumbents on the list of candidates has a positive effect on the use of preference votes. A change to the legislation, however, has reduced the capacity of parties to fill in their lists with a lot of such candidates.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…110 votes for C A in district D A and 90 votes for candidate C B , then the localness effect can be observed at the aggregate level as C A received 121 votes in total (55%) and C B only 99 votes (45%). Consequently, candidates from urban districts with a comparatively high number of voters, in relation to the other urban districts within the electoral districts, should benefit more from their residence at the electoral district level (Put and Maddens, 2015). The fifth hypothesis, thus, focuses on the residence effect at the level of the electoral district:…”
Section: The Case Of Hamburg and Hypothesesmentioning
confidence: 99%
“…Tavits (2010) provided one of the first analyses of this type with a focus on Estonian elections. More recently, Put and Maddens (2015) provide an analysis of localness effects in the flexible list system of Belgium. In addition, the studies by Evans (2012, 2014) and Gorecki and Marsh (2012) focus on the question of how candidate-voter distance affects candidate choice in UK and Irish elections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research indeed shows that candidates who are born locally or have locallevel political experience are not only electorally more successful (e.g. Tavits, 2010;Put and Maddens, 2015), but also considered valuable resources by party selectorates in personalized systems (Nemoto and Shugart, 2013). Other work discusses how and which voters look for local candidates (Jankowski, 2016;Blais and Daoust, 2017;Collignon and Sajuria, 2018).…”
Section: Introductionmentioning
confidence: 99%